2021
DOI: 10.1128/mbio.01074-21
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxidation by a Fused Cytochrome-Porin Common to Diverse Iron-Oxidizing Bacteria

Abstract: Iron is practically ubiquitous across Earth’s environments, central to both life and geochemical processes, which depend heavily on the redox state of iron. Although iron oxidation, or “rusting,” can occur abiotically at near-neutral pH, we find neutrophilic iron-oxidizing bacteria (FeOB) are widespread, including in aquifers, sediments, hydrothermal vents, pipes, and water treatment systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 88 publications
2
57
0
Order By: Relevance
“…For neutrophilic FeOB like ES-1, the Cyc2 Fe(II) oxidation pathway was originally deduced from comparative genomics, and recent work has verified the Fe(II)-oxidizing function of Cyc2 PV-1 ( 29 ), a relatively close homolog of Cyc2 ES-1 . Apart from Cyc2, the rest of the pathway has not been tested in neutrophilic FeOB isolates ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For neutrophilic FeOB like ES-1, the Cyc2 Fe(II) oxidation pathway was originally deduced from comparative genomics, and recent work has verified the Fe(II)-oxidizing function of Cyc2 PV-1 ( 29 ), a relatively close homolog of Cyc2 ES-1 . Apart from Cyc2, the rest of the pathway has not been tested in neutrophilic FeOB isolates ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ES-1, this is cyc2 , and in fact, cyc2 homologs are common across the Fe(II)-oxidizing Gallionellaceae and Zetaproteobacteria ( 26 , 50 , 52 , 54 ). Furthermore, Cyc2 from multiple organisms, including the zetaproteobacterium Mariprofundus ferrooxydans , has been shown to oxidize Fe(II) ( 27 , 29 , 55 ). The cyc2 genes are highly expressed in Fe(II)-oxidizing environments, as shown by metatranscriptomic studies on marine Zetaproteobacteria iron mats ( 52 ) and an Fe-rich aquifer dominated by Gallionellaceae (of which Sideroxydans lithotrophicus ES-1 is a member) ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey of 18 metagenome assemblies from the North Pond crustal aquifer (Tully et al, 2018) using the FeGenie library confirmed the presence of previously reported iron oxidases (Figure 1) (Tully et al, 2018;Seyler et al, 2020), which we phylogenetically linked to Zetaproteobacteria (cyc2) and Rhodospirillaceae (foxE) (Supplementary File 2). Linking cyc2 to Zetaproteobacteria is important because this gene is highly diverse and is often encoded by taxa not known to be capable of iron oxidation; thus, only a handful of cyc2 genes have been experimentally shown to be iron oxidases (Castelle et al, 2008;Jeans et al, 2008;Barco et al, 2015;McAllister et al, 2020a;Keffer et al, 2021). Further, we also documented the presence of genes associated with iron reduction [mtrCAB (Pitts et al, 2003;Hartshorne et al, 2007;Edwards et al, 2020) within seven of the timepoints, which span 2 years (Figure 1)].…”
Section: Resultsmentioning
confidence: 83%
“…The Impact of Shifting Redox Conditions on Iron Cycling in the North Pond Aquifer Recent work, including metagenomic, metatranscriptomic, and colonization/poised-electrode experiments, provide evidence for iron oxidation within the North Pond aquifer. Metagenomic (Tully et al, 2018) and metatranscriptomic (Seyler et al, 2020) studies revealed the presence of genes associated with iron oxidation, specifically, cyc2 [encoding an outer membrane porincytochrome fusion; (Appia-Ayme et al, 1998;Castelle et al, 2008;Barco et al, 2015;He et al, 2017, Keffer et al, 2021] and foxE (encoding a periplasmic cytochrome; Croal et al, 2007;Pereira et al, 2017). Tully et al (2018) also reconstructed metagenomeassembled genomes (MAGs) affiliated with the iron-oxidizing Zetaproteobacteria, which are known to adapt to fluctuating O 2 concentrations and advective flow regimes (Chiu et al, 2017;Blackwell et al, 2020), further solidifying the presence and significant contribution that iron-oxidizing bacteria make to the aquifer community.…”
Section: Resultsmentioning
confidence: 91%